Contextualized School-Based Cognitive Behavioral Therapy (CBT) Intervention for Malaysian Secondary School Students - Saw, Jo Anne; Tam, Cai Lian; Thanzami, Vanlal; Bonn, Gregory (Frontiers in Psychiatry, 2020)
This study investigates the effectiveness of the school-based Shine Through Any Roadblocks (STAR) CBT intervention, by a screening conducted on 634 students from eight secondary schools in Malaysia. Participants (n = 85) who fulfilled the eligibility criteria were assigned randomly to either the intervention group (n = 42) or the assessment-only waitlist control group (n = 43). The intervention consisted of eight group-based sessions over a period of 2 months. Sessions were 60-min each and conducted according to the STAR module. Outcome measures (depressive symptoms and automatic negative thoughts) were administered at five intervals: baseline/pre-intervention, mid-intervention, post-intervention, 1-month after intervention, and 3-months after intervention. Results showed significant and lasting lower levels of depressive symptoms and automatic negative thoughts in the intervention group, indicating that the STAR intervention could be an effective means of reducing depressive symptomatology among adolescents. Clinical implications for the Malaysian secondary school context are further discussed.